Organic, inorganic, and hybrid solar cells : principles and practice - Lin, Ching-Fuh. (Hoboken, NJ : Wiley, 2012)
"Many books discuss inorganic semiconductor solar cells and some books for organic solar cells, but very few books deal with the composite solar cells that use both organic materials and inorganic semiconductors. The authors view organic and inorganic composite thin-film solar cells as the most promising photovoltaic technology for future energy solutions. Focusing on all aspects of realizing low-cost and long life solar cells, the text covers inorganic, organic, and hybrid materials. This unique guide provides an unparalleled description of the functioning principles and fabrication techniques of organic-inorganic composite solar cells"--
"This book will give a detailed description on the organic-inorganic composite solar cells, from the basic principles to practical devices"--
Foreword Preface About the Authors Chapter 1 Introduction Why Solar Energy? Ching-Fuh Lin 1.1 The Era of Fossil Energy 1.1.1 Possible Depletion of Fossil Fuels 1.1.2 Global Warming 1.1.3 Dramatic Change of Weather 1.2 Renewable Energies 1.3 Solar Energy and Economy 1.3.1 Production Issue 1.3.2 Types of Solar Cells 1.3.3 Cost Analysis Grid Parity 1.3.4 Cost Analysis Break Down the System Cost 1.3.5 The Forecast and Practical Trends 1.4 Move toward Thin-Film Solar Cells 1.4.1 Inorganic vs. Organic 1.4.2 More Possible Applications 1.5 Outline of the Book Chapter 2 Light and Its Interaction with Matters Ching-Fuh Lin 2.1 What is Light? 2.1.1 Light Ray 2.1.2 Light as a Wave 2.1.3 Plane-wave Solution of Wave Equation 2.1.4 Wave as a Particle 2.1.5 Black-body Radiation and Solar Spectrum 2.1.6 The Brightness and Intensity of Sunlight 2.2 Fundamentals of Interaction between Light and Matters 2.2.1 Interaction of Electric Field with Dielectrics 2.2.2 Interaction of Light with Magnetic Materials 2.2.3 Summary of Light-Matter Interaction without Energy Exchange 2.3 Basic Properties of Transparent Materials 2.3.1 Reflection and Refraction 2.3.1.1 Boundary Conditions for Electric and Magnetic Fields 2.3.1.2 Reflection and Transmission of Plane Waves 2.3.1.3 Laws of Reflection and Refraction 2.3.1.4 Reflection and Transmission Coefficients 2.3.1.5 Reflectivity and Ratio of Transmitted Intensity 2.3.1.6 Total Reflection 2.3.1.7 Brewster Angle 2.3.2 Polarization 2.3.3 Dispersion 2.3.4 Isotropy and Anisotropy 2.3.5 Scattering 2.3.6 Nonlinear Optics: Energy Up Conversion and Down Conversion 2.4 Interaction of Light and Matters with Energy Exchange 2.4.1 Interaction of Light with Conductors 2.4.2 Quantum Concept of Atomic System 2.4.3 Light-Matter Interactions Chapter 3 Fundamentals of Inorganic Solar Cells Chih-I Wu 3.1. From Atomic Bonds to Energy Bands 3.2 Energy Bands from a Quantum Mechanics Point of View 3.3. The Energy Band in Semiconductors 3.4. PN Junction 3.5 Energy Band Diagram of the PN Junction 3.6 Carrier Transport in a PN Junction 3.6.1 Diffusion 3.6.2 Drift 3.7 PN junction diodes 3.8 Solar Cell Diodes 3.9 Interaction of Light and Materials 3.10 Solar Cell Materials 3.10.1 Crystalline Silicon 3.10.2 GaAs 3.10.3 Thin Film Silicon 3.10.4 Cu-In-Ga-Se (CIGS) 3.10.5 Polymer Solar Cell Materials Chapter 4 Organic Materials Wei-Fang Su 4.1 Bonding and Structure of Organic Molecule 4.2 Properties of Organic Molecules 4.3 Optical Properties of Organic Materials 4.3.1 Absorption 4.3.2 Fluorescence 4.4 Band Gap of Organic Materials 4.5 Electrical Conducting Properties of Organic Materials 4.6 Suitable Organic Materials for Solar Cell Application Chapter 5 Interface between Organic and Inorganic Materials Wei-Fang Su 5.1 Interface between Transparent Electrode and Substrate 5.2 Interface between Transparent Electrode and Active Layer 5.3 Interface between Donor and Acceptor of Active Layer 5.4 Interface between Active Layer and Metal Electrode 5.5 Impedance Characteristics at the Interface Chapter 6 Inorganic Solar Cells I-Chun Cheng 6.1 Introduction 6.2 Basic Principles 6.2.1 P-N Junction in Equilibrium 6.2.2 Current-Voltage Characteristics 6.2.3 Photovoltaic Current-Voltage Characteristics 6.2.4 Series and Shunt Resistances 6.3 Crystalline Silicon Solar Cells 6.4 Thin Film Solar Cells 6.4.1 Amorphous Silicon-Based Thin Film Solar Cells 6.4.2 CdTe Thin Film Solar Cells 6.4.3 CuInSe2 - Based Thin Film Solar Cells 6.5 Outlook Chapter 7 Organic Solar Cells Ching-Fuh Lin 7.1 Dye Sensitized Solar Cell 7.1.1 Structure of DSSC 7.1.2 Principle of DSSC and Development of Dye 7.1.3 Solid-State Dye-Sensitized Solar Cell 7.2 Organic Molecule Solar Cell 7.3 Polymer Solar Cell 7.3.1 Principle of Polymer Solar Cell 7.3.2 Polymer: Fullerene Solar Cell 7.3.3 Effect of Active Layer Morphology on the Performance of Solar Cell 7.3.4 Polymer: Semiconducting Nanoparticle Solar Cell 7.4 Scale Up, Stability and Commercial Development of Organic Solar Cell Chapter 8 Organic-Inorganic Hybrid Solar Cells Ching-Fuh Lin 8.1 Fundamental Concepts for Organic-Inorganic Hybrid Solar Cells 8.2 Sandwiched Structures of the Organic-Inorganic Hybrid Solar Cells 8.2.1 Fabrication of Sandwiched Structures 8.2.2 Performance of Organic-Inorganic Hybrid Solar Cells with Sandwiched Structures 8.2.3 Crystal Phase of Metal Oxides used for Organic-Inorganic Hybrid Solar Cells 8.3 Effect of Mixed-Oxide Modification on Organic-Inorganic Hybrid Solar Cells 8.3.1 Effect of Mixed Oxide on P3HT:PCBM -Inorganic Hybrid Solar Cells 8.3.2 Effect of Mixed Oxides on PV2000-Inorganic Hybrid Solar Cells 8.3.3 Enhancement of Optical Absorption and Incident Photon-to-Electron Conversion Efficiency 8.4 Improvement of Stability 8.4.1 Improvement of Stability Using Mixed Oxides of WO3 and V2O5 8.4.2 Improvement of Stability Using Sol-Gel Processed CuOx 8.5 Organic-Nanostructured-Inorganic Hybrid Solar Cells 8.5.1 Organic-ZnO Nanorod Hybrid Solar Cells 8.5.1.1 Growth of ZnO Nanorods 8.5.1.2 Influence of Drying Time 8.5.1.3 Effect of Additional PCBM Clusters Deposited on ZnO Nanorod Arrays 8.5.2 Effect of Additional Layer of TiO2 Rods Deposited on ZnO Film 8.5.2.1 Effect of NiO Layer 8.5.2.2 Effect of TiO2 Nanorods 8.5.2.3 Influence of TiO2 Nanorods on the Surface Morphology 8.5.2.4 Overall Effect of TiO2 Nanorods on the Device Characteristics 8.6 Hybrid Solar cells using Low-Bandgap Polymers 8.6.1 Low-Bandgap Polymers in the Sandwiched Structure 8.6.2 Improved Stability with Low-Bandgap Polymers in the Sandwiched Structure 8.7 Si Nanowire-Organic Hybrid Solar Cells 8.7.1 Fabrication of SiNWs 8.7.2 The Fabrication of SiNW-organic Hybrid Solar Cells 8.7.3 The Characteristics of SiNW-Organic Hybrid Solar Cells 8.7.4 The Influence of Si NW Length Chapter 9 Outlook of Hybrid Solar Cell Wei-Fang Su References Exercises Index.
engineering bookfair2015
Includes bibliographical references.
Keywords: Solar cells -- Materials; Thin films; Solar cells -- Design and construction; TECHNOLOGY & ENGINEERING / Power Resources / General